Diaspora, remittances, and poverty RP's regions - Ernesto M. Pernia (University of the Philippines, School of Economics (UPSE), 2006)
This paper addresses the question whether and to what extent remittances contribute to poverty alleviation and regional development in the Philippines. It first revisits the causes and consequences of international migration, drawing on the more recent literature. It then zeroes in on remittances in terms of what motivate them and what impact they may have in the labor-sending countries. It proceeds to describe the patterns of labor migration and remittances by region in the Philippines, and then carries out an econometric analysis. The results indicate that remittances appreciably contribute to an improvement in the well-being of the poorest quintile and this effect rises monotonically up to quintile 4, then peters out for the richest 20% of families. Remittances are also good for regional development, but overall increases in regional incomes do not seem to benefit low income families as much as the upper income ones. Remittances have not been entirely an unmixed blessing, however. The diaspora exacts no mean sacrifices for migrant workers and their families. At the national level, the remittance bonanza has conveniently kept the government from pursuing real policy reforms that would have improved the performance of the domestic economy and reduced the need for overseas employment.
Keywords: 330; Region; Rücküberweisung (Migranten); Armutspolitik; Regionale Entwicklung; Philippinen